High salt intake and HIV infection on endothelial glycocalyx shedding in salt-sensitive hypertension - Masenga, Sepiso K.; Liweleya, Situmbeko; Kirabo, Annet (Frontiers in Cell and Developmental Biology, 2024)
The endothelial glycocalyx is closely associated with various physiological and pathophysiological events. Significant modification of the endothelial glycocalyx is an early process in the pathogenesis of cardiovascular disease. High dietary salt and HIV infection damages the endothelial glycocalyx causing endothelial dysfunction and increasing the risk for salt-sensitive hypertension and cardiovascular disease. The two factors, HIV infection and dietary salt are critical independent predictors of hypertension and cardiovascular disease and often synergize to exacerbate and accelerate disease pathogenesis. Salt-sensitive hypertension is more common among people living with HIV and is associated with risk for cardiovascular disease, stroke, heart attack and even death. However, the underlying mechanisms linking endothelial glycocalyx damage to dietary salt and HIV infection are lacking. Yet, both HIV infection/treatment and dietary salt are closely linked to endothelial glycocalyx damage and development of salt-sensitive hypertension. Moreover, the majority of individuals globally, consume more salt than is recommended and the burden of HIV especially in sub-Sahara Africa is disproportionately high. In this review, we have discussed the missing link between high salt and endothelial glycocalyx shedding in the pathogenesis of saltsensitive hypertension. We have further elaborated the role played by HIV infection and treatment in modifying endothelial glycocalyx integrity to contribute to the development of hypertension and cardiovascular disease.